Directed differentiation of human embryonic stem cells to corneal endothelial cell-like cells: A transcriptomic analysis. (October 2016) - Song, Qinglu; Yuan, Songtao; An, Qin; Chen, Yinyin; Mao, Frank Fuxiang; Liu, Yizhi; Liu, Qinghuai; Fan, Guoping
Abstract: Corneal endothelial cells (CECs) are a monolayer of cells covering the inner-side of cornea, playing a pivotal role in keeping the cornea transparent. Because adult CECs have no proliferative capacity, the loss of CECs during aging or under pathological conditions would lead to corneal edema, eventually leading to the blindness. Clinically, donated CECs have been successfully transplanted to treat the diseases of CEC deficiency; however, the source of CEC donation is very limited. As an alternative cell source for CEC transplantation, CEC-like cells can be obtained via in vitro differentiation of human pluripotent stem cells. In this study, we introduced a modified two-stage differentiation method to convert H9 human embryonic stem cells (hESCs) to neural crest cells (NCCs), then further into CEC-like cells. The CEC-like cells treated with bovine CEC conditional medium morphologically best resembled primary CECs among all the culture conditions. By whole transcriptome analysis, we found that the typical markers of CECs, such as Na+-K+-ATPase, AQP1, Col8a and ZO-1, are highly expressed in hESC-derived CEC-like cells. By comparing RNA transcriptome of hESC-derived CEC-like cells with human primary fetal and adult CECs, we further identified shared molecular markers such as TRIT1, HSPB11, CRY1 that can be used to quality control CEC derivatives from hESCs. Our study paves the way for the quality-control and future application of hESC-derived CECs in the treatment of CEC deficiency disorders. Highlights: Introduce a two-stage differentiation method to convert hESCs to the CEC-like cells. Characterize the transcriptome of CEC-like cells via RNA-seq. Compare the similarities/differences among CEC-like cells and human fetal/adult CECs. The transcriptome of CEC-like cells is closer to adult CECs than fetal CECs.